Distribution of persistent organic pollutants (PAHs, Me-PAHs, PCBs) in dissolved, particulate and sedimentary phases in freshwater systems. (November 2015) - Rabodonirina, Suzanah; Net, Sopheak; Ouddane, Baghdad; Merhaby, Dima; Dumoulin, David; Popescu, Tudor; Ravelonandro, Pierre
Abstract: The occurrence of three groups of hazardous organic contaminants (PCBs, PAHs, Me-PAHs) in fifteen watercourses and rivers located in highly urbanized and industrialized zones was studied. The distribution of 62 organic contaminants was determined in three matrices: in the dissolved phase, associated with suspended solid matter (SSM) and in sediment. Their distributions in the aquatic environment depend strongly on their physicochemical properties. Low molecular weight PAHs were predominant in the dissolved phase while those with high molecular weight accumulated preferentially in SSM and sediments. Among the 28 PCBs congeners, only PCB153 was detected. The results showed that the contamination of these areas originated mainly from combustion processes. The three the most polluted sites identified are surrounded by big cities. Ecotoxicological assessment based on the international Sediment Quality Guidelines (SQGs) showed that the toxic effects of the sediment in these watercourses and rivers occurred due to high levels of hydrocarbons. Highlights: Occurrence and source apportionment of PAHs, Me-PAHs, PCBs in freshwater system. Distribution in dissolved, particulate and sedimentary phases of POPs. Assessment of the sediment quality. PAHs may affect on wildlife more significantly than PCBs and Me-PAHs. Abstract : The occurrence, distribution and behavior of PAHs and PCBs in freshwater systems depend strongly on their physicochemical properties.